2019
DOI: 10.1029/2018tc005321
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary Activity of the La Rinconada Fault Zone, San Juan, Argentina

Abstract: Most of the permanent deformation in the Pampean Flat slab segment of the central Andes is taken up at the Andean Orogenic Front in Argentina, a narrow zone between the Eastern Precordillera and Sierras Pampeanas that comprises one of the world's most seismically active thrust zones. Active faults and folds in the region have been extensively mapped but still largely lack information on style and rates of deformation, which is essential for understanding the distribution of regional strain and estimating the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…Hedrick et al () identified alluvial surfaces as old as ~181 +/‐ 29 ka at the Loma Negra fan complex west of the city of San Juan, and ~212 +/‐ 37 ka at the Rinconada‐Carpinteria complex ~25 km to the south of San Juan. Similar results (153.5 +14.6/‐13.7 ka), have been reported by Rimando et al () also for the Rinconada‐Carpintería area. Along the El Tigre fault to the northwest, Siame et al () dated a ~180 +/‐ 38 ka fan, as well as two older surfaces ranging up to ~670 ka.…”
Section: Discussionsupporting
confidence: 90%
“…Hedrick et al () identified alluvial surfaces as old as ~181 +/‐ 29 ka at the Loma Negra fan complex west of the city of San Juan, and ~212 +/‐ 37 ka at the Rinconada‐Carpinteria complex ~25 km to the south of San Juan. Similar results (153.5 +14.6/‐13.7 ka), have been reported by Rimando et al () also for the Rinconada‐Carpintería area. Along the El Tigre fault to the northwest, Siame et al () dated a ~180 +/‐ 38 ka fan, as well as two older surfaces ranging up to ~670 ka.…”
Section: Discussionsupporting
confidence: 90%
“…Assuming zero erosion could be justified by the observed ubiquity of desert varnish, which is an indication of high degree of surface preservation (e.g., Jakica et al, 2011;Rimando et al, 2019). Furthermore, zero erosion has also been assumed in other slip rate studies employing cosmogenic dating in several sites along the Precordillera and the Sierras Pampeanas (Costa et al, 2019;Hedrick et al, 2013;Rimando et al, 2019;Schmidt et al, 2011a;Siame et al, 2002). Alluvial surfaces are more likely than not to have a component of inherited nuclide concentration (e.g., Anderson, Repka, & Dick, 1996;Blisniuk et al, 2012;Brocard et al, 2003;Lal, 1991;Repka et al, 1997).…”
Section: Agesmentioning
confidence: 99%
“…Compared to the thin-skinned structures in the west (e.g., Las Peñas, La Rinconada, and Las Tapias faults, Figure 1; Costa et al, 2019;Siame et al, 2002, and references therein;Rimando et al, 2019), little is known about the rates of movement of most of the basement-cored uplifts of the Sierras Pampeanas. These structures create significant relief in the retroarc region of Argentina (Costa, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term deformation and erosion rates across the Precordillera and adjacent provinces based on own estimated and previously published data (Bohon, Schoenbohm, Brooks, & Costa, 2008; Rimando et al., 2019; Schmidt et al, 2011; Schoenbohm et al., 2013; Siame, Bellier, Sébrier, & Araujo, 2005; Siame et al., 1997, 2002). Black and blue circles represent vertical slip rates and shortening rates, respectively.…”
Section: Tectonic and Seismic Implicationsmentioning
confidence: 99%